Re-Thinking Sustainable Education Systems in Iceland: The Net-University Project - Rennie, Frank; Jóhannesdóttir, Sigurbjörg; Kristinsdottir, Stefania (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The recent economic crisis in Iceland has raised issues of the sustainability of Icelandic higher education to new levels of importance. A key strategy in relation to this economic crisis is to consider the merger of the four public universities in Iceland and to introduce a much higher enegagement with online and open delivery methods of higher education. The Net-University Project was an EU Leonardo-funded initiative to compare approaches to open and distance education in Iceland, Sweden, and Scotland, with additional lessons from Atlantic Canada. In particular, it sought to focus on the transfer of innovation in continuing university education, with particular emphasis on the development and delivery of online higher education courses throughout rural Iceland (i.e., outside of Reykjavik). The partners concentrated on how knowledge and experience about distributed and distance learning models could be transferred between the partner countries and how such models can be integrated into the education system to better support higher education and lifelong learning. There was a particular interest in the practical use of open educational resources (OER) for course design and in the sharing of these course modules among university partners. Some good practice and lessons from OER use in course creation are listed.